(untitled) (KULT_online, 2009)
In her 2007 study, Short Story: Textsorte und Leseerfahrung, Renate Brosch poses the question of what characterises the particular reading experience ("Leseerfahrung") of the short story as a genre ("Textsorte"). Using many and varied examples, she combines concepts of reader response and reception with narratological categories and examines the influence of certain textual features on the reading process. Brosch’s basic assumption is that most short stories differ from longer narrative forms (e.g. the novel) solely in terms of the aesthetic experience or effect they create, especially through their proclivity for visuality and representativeness. With regard to focus and methodology, the study therefore clearly departs from the mainstream of short story theory and could well provide new impetus for study.